IMPROVING GUEST EXPERIENCE: STRATEGIES FOR ENHANCING RECEPTIONIST SERVICES IN HOTELS - Nicholas Kristo Alviziduhu Nanulaitta; Chrisostomus Susmono Widagdo (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The main objective of this study is to investigate the methodologies used by hotels in enhancing their reception services and analyze the subsequent impact on customer satisfaction. The adopted research methodology is qualitative, including surveys and interviews conducted with hotel personnel and actual guests. The research findings reveal that there are many effective strategies to enhance reception services, including staff training, use of cutting-edge technology, improvement of interpersonal and emotional competencies, and optimization of information systems. The implementation of this strategy is anticipated to provide an increased level of guest satisfaction and enhance the hotel's competitive position in the industry. Consequently, a holistic approach to enhancing reception services has the potential to enable hotels to maintain a competitive advantage and strengthen their brand image in the market.